Acceptance of the Internet-Based Sharing Nursing Service among caregivers of elderly with chronic diseases - Ruijie Shan; Zhenhui Wang; Chenjuan Ma; Chunhong Guo; Naixue Cui (BMC, 2024)
Abstract Background In China, Internet-Based Sharing Nursing Service (IBSNS) is a new mode of nursing service delivery that has been in practice for over five years, which enables nurses to provide care at clients' home. However, the acceptance and associated factors of IBSNS among caregivers of elderly with chronic diseases who are the major clients of the service were unclear. Aim To explore the acceptance of IBSNS and its associated factors among Chinese caregivers of elderly patient with chronic diseases based on the modified Technology Acceptance Model (mTAM). Methods A cross-sectional study was conducted from February 2023 to March 2023. Caregivers of hospitalized elderly with chronic diseases were recruited using convenience sampling method from three hospitals in Beijing, China. Data were obtained from self-reports of participants. Structural equation modeling was used to analyze data. Results A total of 65.1% of the caregivers had neutral to weakly positive behavioral intention of IBSNS use. The mTAM model was supported with good model fit. Perceived ease of use was positively associated with perceived usefulness. Both perceived usefulness and perceived security were positively associated with attitude, consequently, attitude was associated with behavioral intention. Conclusions Improving the ease of use, security, and usefulness may be helpful to increase the positive attitude towards IBSNS and behavioral intention of using IBSNS, which provides valuable insights that can help healthcare providers improve the integration of technology in patient care, ultimately leading to better health outcomes and more efficient healthcare systems.